Kesejahteraan Rumah Tangga dalam Pernikahan Jarak Jauh dan Pernikahan Konvensional Perspektif Maqāṣid Sharī’ah - Fazila, Nafiza Nur; Nugroho, Irzak Yuliardy (Komparatif: Jurnal Perbandingan Hukum dan Pemikiran Islam, 2024)
Abstract: This study aims to compare the level of household welfare in Long Distance Marriage (LDM) couples and conventional couples in Sumengko Village, Kwadungan District, Ngawi Regency, based on the perspective of Maqāṣid Sharī'ah. Well-being is measured through two main aspects of Maqāshid Syar̄ah: the preservation of the soul (Ḥifẓ al-Nafs) and the preservation of property (Ḥifẓ al-Māl). This study used a qualitative approach with interviews and observation methods on four couples, consisting of two LDM pairs and two conventional pairs. The data is analyzed comparatively. LDM couples face challenges such as limited communication, emotional management, and physical distance that affect emotional relationships. In contrast, conventional couples face problems in decision-making, daily relationship dynamics, and household financial management. The results of the study show that the household welfare of both types of couples has its advantages and disadvantages, depending on their ability to maintain a balance of soul and property according to the principles of Maqāṣid Sharī'ah. LDM couples show the ability to build independence and emotion management, which is formed from a more structured long-distance communication pattern. In contrast, conventional couples tend to be superior in their day-to-day in-person interactions, but face greater challenges in aligning decisions together, especially when it comes to financial aspects. Keywords: Household Welfare, Long Distance Marriage Couples, Conventional Couples, Maqāṣid Sharī'ah, Ḥifẓ al-Nafs, Ḥifẓ al-Māl. Abstrak: Penelitian ini bertujuan membandingkan tingkat kesejahteraan rumah tangga pada pasangan Long Distance Marriage (LDM) dan pasangan konvensional di Desa Sumengko, Kecamatan Kwadungan, Kabupaten Ngawi, berdasarkan perspektif Maqāṣid Sharī’ah. Kesejahteraan diukur melalui dua aspek utama Maqāshid Syar̄ah: pelestarian jiwa (Ḥifẓ al-Nafs) dan pelestarian harta (Ḥifẓ al-Māl). Studi ini menggunakan pendekatan kualitatif dengan metode wawancara dan observasi terhadap empat pasangan, terdiri dari dua pasangan LDM dan dua pasangan konvensional. Data dianalisis secara komparatif. Pasangan LDM menghadapi tantangan seperti keterbatasan komunikasi, pengelolaan emosi, serta jarak fisik yang memengaruhi hubungan emosional, sedangkan pasangan konvensional menghadapi masalah dalam pengambilan keputusan, dinamika hubungan sehari-hari, dan pengelolaan keuangan rumah tangga. Hasil penelitian menunjukkan bahwa kesejahteraan rumah tangga pada kedua jenis pasangan memiliki kelebihan dan kekurangan masing-masing, tergantung pada kemampuan mereka dalam menjaga keseimbangan jiwa dan harta sesuai prinsip Maqāṣid Sharī’ah. Pasangan LDM menunjukkan kemampuan dalam membangun kemandirian dan pengelolaan emosi, yang terbentuk dari pola komunikasi jarak jauh yang lebih terstruktur. Sebaliknya, pasangan konvensional cenderung lebih unggul dalam interaksi langsung sehari-hari, tetapi menghadapi tantangan yang lebih besar dalam menyelaraskan keputusan bersama, terutama terkait aspek finansial. Kata kunci: Kesejahteraan Rumah Tangga, Pasangan Long Distance Marriage, Pasangan Konvensional, Maqāṣid Sharī’ah, Ḥifẓ al-Nafs, Ḥifẓ al–Māl.